Comparative analysis of PM10 concentrations in Nukus and Tashkent, Uzbekistan: Ground observations, CAMS, and MERRA-2 reanalysis - Rakhmatova Natella; Nishonov Bakhriddin; Shardakova Lyudmila; Amonov Mansur; Belikov Dmitry (E3S Web of Conferences)
This study examines the PM10 concentration in Nukus and Tashkent, Uzbekistan during 2014– 2015 using ground data, CAMS, and MERRA-2 reanalysis. The results show that Nukus has more than twice the average PM10 concentration compared to Tashkent. CAMS better reproduces the observed concentrations, while MERRA-2 overestimates them, especially in winter. CAMS is also superior in capturing medium-term (7–10 days) PM10 peaks. A case study of a dust storm in May 2018 illustrates the ability of CAMS to estimate PM10 spatial distribution, dust dispersion dynamics, and meteorological factors. Therefore, CAMS is the preferred choice for PM10 analysis in areas without ground data in Uzbekistan.